2015
DOI: 10.1109/mcc.2015.78
|View full text |Cite
|
Sign up to set email alerts
|

End-to-End Privacy for Open Big Data Markets

Abstract: The idea of an open data market envisions the creation of a data trading model to facilitate exchange of data between different parties in the Internet of Things (IoT) domain. The data collected by IoT products and solutions are expected to be traded in these markets. Data owners will collect data using IoT products and solutions. Data consumers who are interested will negotiate with the data owners to get access to such data.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 14 publications
(27 reference statements)
0
30
0
Order By: Relevance
“…Calculate the distance between V to V , (9) end if (10) end if (11) end for (12) end for (13) SorttheVMsin V in the increasing order of distance (14) end for (15) Return CV Algorithm 2: VM selection for data placement.…”
Section: Inputmentioning
confidence: 99%
See 3 more Smart Citations
“…Calculate the distance between V to V , (9) end if (10) end if (11) end for (12) end for (13) SorttheVMsin V in the increasing order of distance (14) end for (15) Return CV Algorithm 2: VM selection for data placement.…”
Section: Inputmentioning
confidence: 99%
“…As there are multiple data placement policies for each dataset, the placement policy with the minimum cost, calculated by formula (10), is selected as the final data placement strategy.…”
Section: Definition 3 (Data Placement Strategy Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…Various existing studies have pointed at the risks and challenges of privacy violations for publishing and using open data (Kalidien, Choenni et al 2010, Conradie and Choenni 2014, Janssen and van den Hoven 2015, Perera, Ranjan et al 2015. Some studies have identified privacy risks or policies for organizations in collecting and processing data (Drogkaris, Gritzalis et al 2015, Kao 2015, some have provided decision support for opening data in general (Zuiderwijk and Janssen 2015), and some have focused on releasing information and data on the individual level (James, Warkentin et al 2015).…”
Section: Introductionmentioning
confidence: 99%